Comprehensive Measurement of the Deformation and Failure of Floor Rocks: A Case Study of the Xinglongzhuang Coal Mine. (12th November 2020) - Liu, Hao; Wang, Pu; Zhang, Weihe; Liu, Qiang; Su, Lijun
Abstract : The isolated island panel 10304 of the Xinglongzhuang coal mine was used as the research subject to study the deformation and damage characteristics of the coal seam floor. The damage of the floor was studied using the borehole strain sensing method and borehole imaging technology, and FLAC3D was used to study the influence of abutment pressure on floor failure. The result shows that the floor under the superimposed area which is affected by lateral and advanced abutment pressure is damaged firstly, and the maximum depth reaches 26 m, other areas of the working face about 23 m. The degree of deformation and failure of floor rock at different depths is decreased. The deformation damage increases with the advancement of the working face until a certain distance at the same depth. The hole image can clearly show the influence range of the abutment pressure in front of the coal wall and influence the degree of the advancement and lag by means of the strain increment curve for each sensor probe and the images from different drilled positions. On the basis that the results of simulation and field measurement are consistent, the results can reflect the three-dimensional failure characteristics of the whole island working face floor in the process of coal mining more comprehensively and accurately; moreover, they also can provide important information for mine flood prevention and ecological environment protection.